When Authenticity Goes Missing: How Monocultural Children's Literature Is Silencing the Voices and Contributing to Invisibility of Children from Minority Backgrounds - Helen Adam (MDPI AG, 2021)
The importance of recognising, valuing and respecting a child's family, culture, language and values is central to socially just education and is increasingly articulated in educational policy worldwide. Inclusive children's literature can support children's human rights and contribute to equitable and socially just outcomes for all children. However, evidence suggests many educational settings provide monocultural book collections which are counterproductive to principles of diversity and social justice. Further, that educators' understandings and beliefs about diversity can contribute to inequitable provision and use of diverse books and to inequitable outcomes of book sharing for many children. This paper reports on a larger study investigating factors and relationships influencing the use of children's literature to support principles of cultural diversity in the kindergarten rooms of long day care centres. The study was conducted within an ontological perspective of constructivism and an epistemological perspective of interpretivism informed by sociocultural theory. A mixed methods approach was adopted, and convergent design was employed interpret significant relationships and their meanings. Twenty-four educators and 110 children from four long day care centres in Western Australia participated. Data were collected through semi-structured interviews, video-based observations, field notes, document analysis and a book audit. This study firstly identified that current book collections in kindergarten rooms of long day care centres promote mono-cultural viewpoints and 'othering' of minority groups through limited access to books portraying inclusive and authentic cultural diversity. Secondly, that educators had limited understandings of the role of literature in acknowledging and valuing diversity and rarely used it to promote principles of diversity, resulting in a practice of "othering" those from minority group backgrounds. The key challenges which emerged from the study concerned beliefs, understanding and confidence of educators about diversity and inclusion, and the impact of these on their approaches to promoting principles of diversity through the use of children's books. This research contributes to discussion on the value of children's literature in achieving international principles of diversity. These findings have important social justice implications. The outcomes of this study have implications for educators, policy makers, early childhood organisations and those providing higher education and training for early childhood educators.